Applications of Magnetohydrodynamic Couple Stress Fluid Flow between Two Parallel Plates with Three Different Kernels. (26th October 2021) - Siddique, Imran; Akgül, Ali; Kahsay, Hafte Amsalu; Tsegay, Teklay Hailay; Wubneh, Kahsay Godifey
Abstract : In this paper, we investigate the implementations of newly introduced nonlocal differential operators as convolution of power law, exponential decay law, and the generalized Mittag-Leffler law with fractal derivative in fluid dynamics. The new operators are referred as fractal-fractional differential operators. The governing equations for the problem are constructed with the fractal-fractional differential operators. We present the stability analysis and the error analysis.